Clinical potential of eluxadoline in the treatment of diarrhea-predominant irritable bowel syndrome - Sobolewska-Włodarczyk A; Włodarczyk M; Storr M; Fichna J (Dove Medical Press, 2016)
Aleksandra Sobolewska-Włodarczyk,1 Marcin Włodarczyk,1 Martin Storr,2 Jakub Fichna1 1Department of Biochemistry, Faculty of Medicine, Medical University of Lodz, Lodz, Poland; 2Center of Endoscopy, Starnberg, Germany Abstract: Diarrhea-predominant irritable bowel syndrome (IBS-D) belongs to the group of functional gastrointestinal disorders and is characterized by abdominal pain in conjunction with diarrhea. The incidence of IBS-D is currently increasing, leading to a heavy economic burden for patients and health care systems worldwide. Recent studies suggest eluxadoline as an attractive new tool for the treatment of patients with IBS-D. Eluxadoline is an orally active µ- and κ-opioid receptor agonist and δ-opioid receptor antagonist, with powerful antidiarrheal and analgesic activity. Eluxadoline is believed to act locally in the enteric nervous system, and has no adverse effects in the central nervous system. In this review, we discuss the most recent findings on the mechanism of action of eluxadoline and the results of the clinical trials in patients with IBS-D. We also discuss possible side effects and analyze the potential of eluxadoline to be used in the treatment of IBS-D. Keywords: abdominal pain, health care, functional gastrointestinal disorders, IBS, constipation, discomfort